Dynamic imaging of MYC and CDKN1A mRNAs as an indicator of cell G1-phase arrest. Issue 11 (24th January 2017) - Yi, Linglu; Lin, Xuexia; Li, Haifang; Ma, Yuan; Lin, Jin-Ming
Abstract : A live-cell mRNA imaging method to dynamically identify cell transition stage G1-phase arrest. Abstract : The identification of G1-phase arrest requires a dynamic capturing method. In this work, we reported an indicator based on MYC and CDKN1A mRNA imaging to visualize G1-phase cycle arrest. A typical G1-phase arrest imaging is shown as a green-to-red conversion by fluorescence molecular beacons indicating the change as down-regulating of MYC and up-regulating of CDKN1A mRNA. We performed G1-phase arrest imaging on proliferated cancer cells inhibited by TMPyP4 and explore the role of HIF-1α in the proliferation inhibition effect.